1993
DOI: 10.1159/000187254
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-Induced Sialadenitis: Report of 4 Cases and Review of the Literature

Abstract: Sialadenitis after administration of iodine compounds is rare. In this paper we report 4 hemodialysis patients who suffered from this rare manifestation of iodism and review the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
(8 reference statements)
0
8
0
3
Order By: Relevance
“…However, delayed reactions have been reported in relation to CM retention, such as vasculitis, iodine mumps or iododerma (4,10,15). CM should therefore be removed as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, delayed reactions have been reported in relation to CM retention, such as vasculitis, iodine mumps or iododerma (4,10,15). CM should therefore be removed as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…DONNELLY et al reported a patient undergoing continuous ambulatory peritoneal dialysis to develop bilateral submandibular swelling 20 hours after injection of iopamidol(5). RIVERA et al encountered 2 cases of sialoadenitis after iohexol administration in HD patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…There is one case of submandibular swelling (13), and four cases of ‘‘iodine mumps’’ (14) thought related to iodine exposure in patients with ESRD. In this report, two of the ESRD patients received iodine through the intake of an oral preparation for bronchitis, while the other two cases had recently received fistula arteriograms (15).…”
Section: Radiocontrast Removal With Hemodialysismentioning
confidence: 89%